1999
DOI: 10.2106/00004623-199912000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Between Septic Arthritis and Transient Synovitis of the Hip in Children

Abstract: Background: A child who has an acutely irritable hip can pose a diagnostic challenge. The purposes of this study were to determine the diagnostic value of presenting variables for differentiating between septic arthritis and transient synovitis of the hip in children and to develop an evidence-based clinical prediction algorithm for this differentiation. Methods: We retrospectively reviewed the cases of children who were evaluated at a major tertiary-care children's hospital between 1979 and 1996 because of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
351
9
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(394 citation statements)
references
References 25 publications
5
351
9
10
Order By: Relevance
“…2011;46(Suppl 4): [14][15][16][17][18][19][20] Figura 1 -Paciente masculino, 6a5m, radiografia de bacia panorâmica nas projeções em AP e Lauenstein, com história de febre, dor, claudicação e limitação funcional do quadril esquerdo há dois dias (A, B). Pós-operatório de 2a2m, paciente sem queixas e radiografia sem alteração.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…2011;46(Suppl 4): [14][15][16][17][18][19][20] Figura 1 -Paciente masculino, 6a5m, radiografia de bacia panorâmica nas projeções em AP e Lauenstein, com história de febre, dor, claudicação e limitação funcional do quadril esquerdo há dois dias (A, B). Pós-operatório de 2a2m, paciente sem queixas e radiografia sem alteração.…”
Section: Resultsunclassified
“…Eich et al (16) desenvolveram seu algoritmo orientados pelo derrame articular do quadril e pelo menos dois dos seguintes critérios: temperatura retal maior que 38 graus, VHS maior que 20mm/h e PCR maior que 20mg/L. Kocher et al (17) usaram quatro preditores para o diagnóstico diferencial de sinovite transitória e AS do quadril: história de febre, recusa em apoiar o membro inferior acometido, VHS maior que 40mm/h e contagem de leucócitos maior que 12.000cels/mm 3 . Eles encontraram um valor preditivo para AS de 40% quando os pacientes apresentavam dois critérios, 93,1% para três, e 99,6% para quatro critérios concomitantes.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…[10][11][12][13] For the performance of the proposed flowchart it was necessary to adapt some parameters used in the studies found in literature. Fever, for example, was measured by the oral temperature in the studies by Kocher et al 27,28 , Falzon et al 29 and Caird et al 18 , yet this is not evaluated in most orthopedic services in Brazil and, we therefore use the axillary temperature of 37.8 °C. 30 The leukocytosis used in the proposed flowchart (>12000cells/mm³) is justified by the greater ethnic similarity between the Brazilian population and that of the studies that used the same cut-off point, in comparison to the Korean population that considers a lower value of leukocytosis (11000cells/mm³).…”
Section: Discussionmentioning
confidence: 99%
“…In differentiating between septic arthritis and transient synovitis of the hip in children, Kocher et al [1] stratified the risk of septic arthritis in children according to the presence of a number of clinical and serological parameters, which seems to work well in the clinical situation. Therefore, we suggest a similar approach in tackling the problem of deep periprosthetic infections.…”
mentioning
confidence: 99%